Total events and net clinical benefit of rivaroxaban and aspirin in patients with chronic coronary or peripheral artery disease: The COMPASS trial - Branch, Kelley R H; Probstfield, Jeffrey L; Bosch, Jackie; Bhatt, Deepak L; Maggioni, Aldo P; Muehlhofer, Eva; Avezum, Alvaro; Widimsky, Petr; Connolly, Stuart J; Yi, Quilong; Shestakovska, Olga; Yusuf, Salim; et al. (The American heart journal, 2023)
BACKGROUND: Low dose rivaroxaban with aspirin reduced major cardiovascular events (MACE) compared to aspirin alone in patients with cardiovascular disease although effects on total events are unknown. METHODS: The COMPASS clinical trial randomized 27,395 participants with chronic coronary and/or peripheral artery disease to rivaroxaban 2.5 mg twice daily plus aspirin 100 mg daily, rivaroxaban 5 mg twice daily alone, or aspirin 100 mg daily. We analyzed total (first and recurrent) MACE outcomes of cardiovascular death, stroke, or myocardial infarction, and the primary safety outcome of major bleeding. Exploratory analyses included on-treatment and net clinical benefit. Total MACE and safety events were modeled for each treatment. RESULTS: MACE events were lowest in rivaroxaban with aspirin (379 first MACE, 432 total MACE) compared with rivaroxaban (448 first, 508 total) or aspirin alone (496 first, 574 total). Rivaroxaban and aspirin reduced total MACE events compared with aspirin alone [HR 0.75, 95% CI 0.66-0.85, P < .0001, number needed to treat for 2 years (NNT2y) of 63]. Total major bleeding was higher for rivaroxaban with aspirin compared to aspirin, but severe bleeding was not increased. The net clinical benefit of rivaroxaban plus aspirin was 20% higher compared with aspirin alone [HR 0.80 (95% CI 16.3%-31.6%)]. Rivaroxaban alone had no benefit on MACE outcomes compared with aspirin alone. MACE outcomes were similar for those on and off randomized treatment. CONCLUSIONS: Low dose rivaroxaban with aspirin significantly reduces first and total cardiovascular events compared with aspirin alone with a NNT2y of 63 and a 20% net clinical benefit. TRIAL REGISTRATION: NCT01776424. https://clinicaltrials.gov/ct2/show/NCT01776424.
Keywords: onemocnění periferních arterií; inhibitory agregace trombocytů; krvácení; Humans; Hemorrhage; lidé; rivaroxaban; Rivaroxaban; nemoci koronárních tepen; Drug Therapy, Combination; Factor Xa Inhibitors; Platelet Aggregation Inhibitors; inhibitory faktoru Xa; Peripheral Arterial Disease; Aspirin; Coronary Artery Disease; kombinovaná farmakoterapie